La descolonización y el giro des-colonial (Tema Central) - Maldonado Torres, Nelson (2006)
The subject of decolonization is assuming a position of great importance in today’s political processes. Apart from providing some indications about the places in which such discourse have become relevant, this article also explores the profound significance, in particular, the epistemic and theoretical, of the concept of decolonization. In this sense, the article continues the discussion on undertaken by others about the “decolonization of knowledge” and other related themes. It’s intents is through the concepts of de-colonial attitude and de-colonial reason, attempt to establish the bases for a wider comprehension of the decolonization with clear consequences for political and theoretical work.